Predictors of in-hospital mortality in patients with infective endocarditis. Issue 6 (3rd September 2021) - Suwa, Yoshinobu; Miyasaka, Yoko; Taniguchi, Naoki; Harada, Shoko; Nakai, Eri; Shiojima, Ichiro
Abstract: Background: Infective endocarditis is a serious septic disease, and the epidemiological profile has changed over the last decade. However, there is a paucity of data regarding the current outcome and predictor of in-hospital mortality in patients with infective endocarditis. Methods: Consecutive patients diagnosed as infective endocarditis based on the modified Duke criteria at Kansai Medical University hospital from January 2006 to June 2019 were prospectively included. The primary outcome was in-hospital mortality. Cox proportional hazards modelling was used to assess risk factors of in-hospital mortality. Results: Of 137 consecutive patients with infective endocarditis (age 60 ± 17 years-old, 62% men, 65% underlying cardiac disease, 11% chronic haemodialysis), 18 (13%) died during hospitalisation. Age and sex were not associated with in-hospital mortality. Patients on chronic haemodialysis exhibited significantly higher in-hospital mortality rate than those without (47 vs. 9%). After adjusting for comorbidities in a multivariate Cox proportional hazards model, chronic haemodialysis was a significant predictor of in-hospital mortality [hazard ratio (HR) 4.22, 95% confidential interval (CI): 1.49–12.0, p < 0.01], independently of C-reactive protein (per 1 mg/dl; HR 1.07, 95%CI: 1.02–1.12, p < 0.05). Conclusions: Infective endocarditis in patients on chronic haemodialysis is a serious life-threatening condition that requires early diagnosis and an effective therapeutic approach.